(untitled) (Al-Academy, 2022)
The use of different materials in the art of ceramics is considered a new form of contemporary philosophical trends. That was introduced to art as a result of societal changes and transformations and rapid technological development. And it plays a very essential part in the beauty of the artistic structure. The contrast of using different materials in ceramics is considered a part of the old historical achievements since the art of ceramics used to follow strict standards. Which does not apply to contemporary ceramic, Because recently, it has become free from any religious and social control and created a whole new intellectual context, heading to new horizons in which it works with the newly added materials as a strategy to ensure the activation of all sensual, structural, and aesthetic aspects. And ensures the importance of the artist’s individuality, and realizes their identity and the essential part they have in the exploratory practices and the growth of the technical performance, as well as inventing new artistical and structural material. As a whole, this illustrates the development of the intellectual context of the artist, the art piece, and the art admirers.The subject of this research aims to reveal the improved aspects of the intellectual context, that came as a result of the contrast of materials and clays, and demonstrate the current status of contemporary ceramic, And its remarkable ability to continuously add to the shape and significance